2015
DOI: 10.1007/s00402-015-2300-0
|View full text |Cite
|
Sign up to set email alerts
|

Radial nerve location at the posterior aspect of the humerus: an anatomic study of 100 specimens

Abstract: We present the OF as an osseous landmark to reduce the risk of iatrogenic radial neuropathy. HL and TW can be reliably used to estimate the RN location. The consistent "safe zones" of the RN in relation to the OF are 10.5 cm at the medial edge, 9 cm at the center and 7.5 cm at the lateral edge of the posterior aspect of the humeral shaft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Additionally, using embalmed cadaveric specimens may have represented a potential limitation: formalin causes shrinkage and dehydration of soft tissue structures, primarily affecting their neurovascular supply, which may alter anatomical measurements. 8,15,27,28 Moreover, disarticulation of the shoulder joint and dissection of the radial nerve to reach sufficient exposure may have affected the native course of the nerve. 8,15 Therefore, we conducted an in vivo anatomical study based on CTA that we believe overcomes these reported drawbacks associated with the use of cadaveric specimens, and we utilized 3D reconstruction of CT scan images of living subjects to simulate the in situ conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, using embalmed cadaveric specimens may have represented a potential limitation: formalin causes shrinkage and dehydration of soft tissue structures, primarily affecting their neurovascular supply, which may alter anatomical measurements. 8,15,27,28 Moreover, disarticulation of the shoulder joint and dissection of the radial nerve to reach sufficient exposure may have affected the native course of the nerve. 8,15 Therefore, we conducted an in vivo anatomical study based on CTA that we believe overcomes these reported drawbacks associated with the use of cadaveric specimens, and we utilized 3D reconstruction of CT scan images of living subjects to simulate the in situ conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the segment where there was direct contact of the radial nerve with the posterior humeral shaft because this segment is reported as the most frequent area of iatrogenic radial nerve injury when using the posterior approach to treat humeral shaft fractures because of the intimate relationship of the radial nerve with the humeral shaft and less mobility. 7 9,17,18…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hackl et al [22] conducted an anatomic study regarding the course of the radial nerve at the posterior aspect of the humeral shaft. They found the ratio which divides humeral length by distance of the proximal edge of the olecranon fossa to lateral edge of the spiral groove was 3.1±0.31, which was similar to our result (2.98±0.27).…”
Section: Discussionmentioning
confidence: 99%